Calculation of ultimate bearing capacity and analysis of bearing characteristics for pile group foundation to underlying offset cave - Yan Zhao; Jiaxing Tao; Pu Li; Lujun Yin; Zhuang Zhang; Haiqin Yan; Wenzhe Zhang; Shuqi Ma; Jinglei Liu; Hailong Wang (PLoS ONE, 2026)
Based on the pile group effect and the principle of limit analysis, a equation is derived for calculating the ultimate bearing capacity of pile group foundations under the condition of offset karst caves beneath. Relying on the pile foundation project in the Guangzhou Baiyun District Science, this study conducts an analysis of the ultimate bearing capacity and bearing characteristics of pile group foundations under karst terrain conditions. The results indicate that an increase in the offset distance of the underlying karst cave leads to a higher ultimate bearing capacity of the pile group foundation. The results of the comparative analysis demonstrate that the proposed method for calculating the ultimate bearing capacity of pile groups is reliable. This method is suitable for evaluating the ultimate bearing capacity and performing safety checks of pile group foundations under the condition of offset karst caves.